The impact of global megatrends on tourism industry - Vlatka Bilas; Sanja Franc; Marija Vukoja (UTMS Journal of Economics, 2022)
The future of tourism industry will be affected by major social, economic, political, environmental, and technological changes, bringing new and often unseen challenges, threats and opportunities. The speed of technological progress has changed societal expectations and at the same time is rapidly surpassing society's ability to adapt. These megatrends are slowly forming but will have deep and long-term effects on all economic sectors, including tourism. The main aim of this paper is to analyze global megatrends and their impact on tourism. After analyzing current megatrends, they are also discussed from the perspective of potential source of innovation in tourism. Having in mind current global environment, the issue of sustainability in tourism is considered, and certain conclusions and recommendations are put forth. The conclusion is that tourism is strategically important and complex sector in many countries. Future development should be based on nurturing and developing a supportive environment for tourist demand, infrastructure, more efficient combination of available resources and valorization of natural, cultural, and historical heritage, but also by stimulating social innovation and entrepreneurship.
Keywords: F01; Z32; 330; tourism industry; global megatrends; sustainable development